Trends from 1996 to 2007 in incidence and mortality outcomes of heart failure after acute myocardial infarction: A population-based study of 20 812 patients with first acute myocardial infarction in Western Australia - Hung, J.; Teng, T.; Finn, Judith; Knuiman, M.; Briffa, T.; Stewart, S.; Sanfilippo, F.; Ridout, S.; Hobbs, M. (Wiley-Blackwell Publishing, Inc., 2013)
Background: Advances in treatment for acute myocardial infarction (AMI) are likely to have had a beneficial impact on the incidence of and deaths attributable to heart failure (HF) complicating AMI, although limited data are available to support this contention.Methods and Results: Western Australian linked administrative health data were used to identify 20 812 consecutive patients, aged 40 to 84 years, without prior HF hospitalized with an index (first) AMI between 1996 and 2007. We assessed the temporal incidence of and adjusted odds ratio/hazard ratio for death associated with HF concurrent with AMI admission and within 1 year after discharge. Concurrent HF comprised 75% of incident HF cases. Between the periods 1996–1998 and 2005–2007, the prevalence of HF after AMI declined from 28.1% to 16.5%, with an adjusted odds ratio of 0.50 (95% CI, 0.44 to 0.55). The crude 28-day case-fatality rate for patients with concurrent HF declined marginally from 20.5% to 15.9% (P<0.05) compared with those without concurrent HF, in whom the case-fatality rate declined from 11.0% to 4.8% (P<0.001). Concurrent HF was associated with a multivariate-adjusted odds ratio of 2.2 for 28-day mortality and a hazard ratio of 2.2 for 1-year mortality in 28-day survivors. Occurrence of HF within 90 days of the index AMI was associated with an adjusted hazard ratio of 2.7 for 1-year mortality in 90-day survivors.Conclusions: Despite encouraging declines in the incidence of HF complicating AMI, it remains a common problem with high mortality. Increased attention to these high-risk patients is needed given the lack of improvement in their long-term prognosis.